Negative Inotropic and Chronotropic Effects of Phenolic Fraction from Cynodon dactylon (linn) on Isolated Perfused Frog Heart (Journal of Scientific Research, 2012)
Cynodon dactylon (L.) Pers belongs to the family Poaceae is a grass native to North Africa, Asia and Australia and southern Europe. The phenolic fraction of Cynodon dactylon (Linn) (CDP) was evaluated for its cardio-protective activity using isolated frog´s heart perfusion method. The negative inotropic and chronotropic activities were recorded using kymograph. The CDP produced negative inotropic and chronotropic actions on isolated frog heart. The pharmacological effect was selectively inhibited by atropine indicating that these might have been mediated through muscarinic receptor.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i3.8549 J. Sci. Res. 4 (3), 657-663 (2012)